Ethnobotanical study of medicinal plants used in Ahar-Arasbaran (protected area in East Azerbaijan Province of Iran) - Ebadi, Mostafa; Eftekharian, Rosa (Mediterranean Botany, 2019)
Iran is an ancient country in the usage of medicinal plants and Ahar is known as one of the richest regions of medicinal plants. The traditional knowledge about medicinal plants is the basic step in many drug productions and these kinds of information should be documented through botanical investigations. The present study is the first survey conducted in this region and its primary point is to distinguish such plants and to present their application in traditional medicine. In this study, the data was gathered by talking with indigenous individuals to identify medicinal plants with local importance developed during the 2015 and 2016 growing seasons. Scientific names and therapeutic uses are also mentioned. The results obtained from the present study indicated that there were 45 medicinal species of 23 families in Ahar and local people mainly used Lamiaceae and Asteraceae then Rosaceae, Brassicaceae and Fabaceae medicinal taxa. Medicinal plants were mostly used to treat intestinal-digestive disorders, for cold treatment and for soothing pain. According to results, significant ethnobotanical data on medicinal plants gives premise information to future pharmacological and phytochemical studies. Also, this document can be utilized as a part of protecting indigenous knowledge.